Activity Test of Extract Edible Bird’s Nest (Aerodramus fuciphagus) as a Natural Treatment to Lower LDL Levels - Musdalifah; Andi Nur Zam Zam; Andi Dian Astriani (Postgraduate, University of Mataram, 2025)
This study aimed to evaluate the effect of edible bird’s nest (EBN) infusion (Aerodramus fuciphagus) on lowering low-density lipoprotein (LDL) levels in white rats (Rattus norvegicus) induced with hypercholesterolemia. Fifteen male Wistar rats were divided into five groups: negative control (distilled water), positive control (simvastatin 10 mg/kg BW), and three treatment groups receiving EBN infusion at doses of 10, 20, and 40 mg/200 g BW. LDL levels were measured before and after treatment using an enzymatic colorimetric method. The results showed that EBN infusion reduced LDL levels in all treatment groups, with the highest decrease at a dose of 40 mg/200 g BW (34.03%), followed by 20 mg (33.46%) and 10 mg (28.13%). Simvastatin, however, produced a greater LDL reduction (55.64%). In conclusion, EBN infusion can reduce LDL levels in hypercholesterolemic rats, particularly at doses of 20 mg/200 g BW, suggesting its potential as a natural lipid-lowering agent, although it is less effective than simvastatin.